Directional deficits in reactive postural control during perturbations among groups of chronic ankle instability, ankle sprain coper, and healthy control - Min Jun Kim; Sehee Kim; Junyoung Kim; J. Ty Hopkins; Wiha Choi; Sehoon Oh; S. Jun Son (Scientific Reports)
Abstract Unanticipated postural control measures may better identify mechanisms of ankle sprains in real-life situations. The purpose of this study was to identify directional deficits in reactive postural control during unanticipated horizontal perturbations among groups of chronic ankle instability (CAI), ankle sprain coper, and healthy control. Sixty-eight volunteers (24 CAI patients, 23 ankle sprain copers, and 21 healthy controls) participated in this study. The participants performed a single-leg stance with unanticipated horizontal perturbations in four random directions of anterior, posterior, medial, and lateral. Anterior-posterior time to stabilization (APTTS) and medial-lateral time to stabilization (MLTTS) were calculated as an indicator of reactive postural control during horizontal perturbations. A significant interaction effect of the group x perturbation directions (3 × 4) was found. Both CAI and ankle sprain coper groups showed longer APTTS and MLTTS during medial and lateral horizontal perturbations compared to the healthy control group. However, no difference was found in APTTS and MLTTS during anterior and posterior horizontal perturbations between three groups. Directional deficits in reactive postural control during medial and lateral perturbations could result from sensorimotor dysfunction as consequences of lateral ankle sprains in the CAI and ankle sprain groups.